Predição e medição de sinais de TV digital na faixa de UHF em ambientes internos - Fernandes, William Douglas Costa (2012)
This work presents an analysis of signal propagation of Digital TV on the UHF range in indoor environments. Based on the comparison of some indoor and outdoor propagation models described on the literature, an algorithm was developed with the aim of generating a signal coverage map that exhibits the reception power on the indoor environment. These simulations were compared with field measurements divided in two case studies. The first one evaluates the signal coverage in an entire floor of one building and the second one inside a single room. It was proved that the propagation models that were extended to the UHF range can be used with high accuracy to determine the reception power level of the digital TV signal.